Mutant Phosphodiesterase 3A Protects From Hypertension-Induced Cardiac Damage. Issue 23 (19th October 2022) - Ercu, Maria; Mücke, Michael B.; Pallien, Tamara; Markó, Lajos; Sholokh, Anastasiia; Schächterle, Carolin; Aydin, Atakan; Kidd, Alexa; Walter, Stephan; Esmati, Yasmin; McMurray, Brandon J.; Lato, Daniella F.; et al.
Abstract : Background: Phosphodiesterase 3A ( PDE3A ) gain-of-function mutations cause hypertension with brachydactyly (HTNB) and lead to stroke. Increased peripheral vascular resistance, rather than salt retention, is responsible. It is surprising that the few patients with HTNB examined so far did not develop cardiac hypertrophy or heart failure. We hypothesized that, in the heart, PDE3A mutations could be protective. Methods: We studied new patients. CRISPR-Cas9–engineered rat HTNB models were phenotyped by telemetric blood pressure measurements, echocardiography, microcomputed tomography, RNA-sequencing, and single nuclei RNA-sequencing. Human induced pluripotent stem cells carrying PDE3A mutations were established, differentiated to cardiomyocytes, and analyzed by Ca 2+ imaging. We used Förster resonance energy transfer and biochemical assays. Results: We identified a new PDE3A mutation in a family with HTNB. It maps to exon 13 encoding the enzyme's catalytic domain. All hitherto identified HTNB PDE3A mutations cluster in exon 4 encoding a region N-terminally from the catalytic domain of the enzyme. The mutations were recapitulated in rat models. Both exon 4 and 13 mutations led to aberrant phosphorylation, hyperactivity, and increased PDE3A enzyme self-assembly. The left ventricles of our patients with HTNB and the rat models were normal despite preexisting hypertension. A catecholamine challenge elicited cardiac hypertrophy in HTNB rats only to the level of wild-type rats and improved the contractility of the mutant hearts, compared with wild-type rats. The β-adrenergic system, phosphodiesterase activity, and cAMP levels in the mutant hearts resembled wild-type hearts, whereas phospholamban phosphorylation was decreased in the mutants. In our induced pluripotent stem cell cardiomyocyte models, the PDE3A mutations caused adaptive changes of Ca 2+ cycling. RNA-sequencing and single nuclei RNA-sequencing identified differences in mRNA expression between wild-type and mutants, affecting, among others, metabolism and protein folding. Conclusions: Although in vascular smooth muscle, PDE3A mutations cause hypertension, they confer protection against hypertension-induced cardiac damage in hearts. Nonselective PDE3A inhibition is a final, short-term option in heart failure treatment to increase cardiac cAMP and improve contractility. Our data argue that mimicking the effect of PDE3A mutations in the heart rather than nonselective PDE3 inhibition is cardioprotective in the long term. Our findings could facilitate the search for new treatments to prevent hypertension-induced cardiac damage.